SPAWNING PERFORMANCE AND EMBRYONIC DEVELOPMENT OF RED EMPEROR SNAPER (Lutjanus sebae) - Philip Teguh Imanto; Regina Melianawati; Made Suastika (Indonesian Aquaculture Journal, 2006)
Snapper is one of economical marine ............